How to Optimally Prepare the Patient for a Facelift Procedure - Mariani, Marta; Fabbri, Mariachiara; Serra, Pietro Luciano; Botti, Chiara; Botti, Giovanni (Facial Plastic Surgery, 2025)
Facelift surgery is among the most commonly performed aesthetic procedures. Achieving optimal outcomes requires careful preoperative planning, particularly in managing airway positioning and maintaining a clean surgical field from the forehead to the neck.This study aims to outline standardized perioperative protocols for facelift surgery, hypothesizing that such measures improve surgical access and reduce intraoperative complications.Retrospective case series (N > 5) conducted by senior authors. The study adheres to STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines for observational studies.Patients undergoing facelift under general anesthesia with endotracheal intubation were reviewed. Focus was placed on tube positioning, scalp access, and hair management. No institutional review board approval was required.Standardized protocols enhanced tube stability, optimized exposure, and minimized operative delays.Precise airway management and field preparation are essential for efficient, safe facelift surgery and should be standardized in clinical practice.
Keywords: facial rejuvenation; cervicofacial lift; SMAS; patient preparation; patient care